Educational Training on the Preparation of Herbal Gel from Rambusa Leaves (Passiflora foetida L.) in Managing Minor Wounds in Sei Pematang Pasir Village, Medan - Desi Alviolina; Eldesi Medisa IlmawatI; Wahidah wahidah; indah Almaidah; Nur Aini (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2026)
Minor wounds are among the most common health problems experienced by communities in daily life. Inadequate first aid management may increase the risk of infection and delay the healing process. Community empowerment through health education and the utilization of local medicinal plants is a strategic approach to improving self-reliance in wound care. This community service program aimed to evaluate the effectiveness of education and training on the preparation of herbal gel from rambusa leaves (Passiflora foetida L.) as an alternative first-aid treatment for minor wounds. A quantitative pre-experimental study with a one-group pretest–posttest design was conducted among 100 participants in Sei Pematang Pasir Village, Medan Labuhan District, Indonesia. Participants received interactive lectures, demonstrations, hands-on practice, discussions, and educational leaflets. Knowledge was assessed using pretest and posttest questionnaires, while practical skills were evaluated through observation checklists. Data were analyzed using descriptive statistics and a paired sample t-test. The proportion of participants with good knowledge increased from 14.0% before the intervention to 85.0% afterward. The mean knowledge score improved significantly from 60.2 ± 9.8 to 88.7 ± 7.2, with a mean difference of 28.5 points (p < 0.001). Furthermore, 88.0% of participants demonstrated good skills in preparing the herbal gel, and participation remained high throughout all program activities. These findings indicate that education and practical training effectively enhanced community knowledge and skills in utilizing Passiflora foetida L. as a herbal gel for minor wound management, supporting community empowerment and the sustainable use of family medicinal plants (TOGA) in primary health care.